2014
DOI: 10.1080/21551197.2014.927305
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Liking of Pureed Food Between Two Groups of Older Adults

Abstract: Cognitive difficulties make consumer testing with older adults who have dysphagia extremely difficult. Using a healthier older adult population to predict liking scores of this subgroup of older adults could provide a reliable method of determining liking in this population. Forty-five adults older than 65 years who had not been diagnosed with dysphagia participated in a taste test at a local seniors' center. Twelve puree consumers were recruited from five long-term care homes in Ontario. All participants rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…However, perceptions of consumers are different from healthy older adults (6,15,16) and where possible, effort needs to be made to capture their liking. Prior work by this team has identified that persons with dysphagia who have sufficiently adequate cognition can communicate their preferences with the modified Cued Facial Scale (16).…”
Section: Sensory Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, perceptions of consumers are different from healthy older adults (6,15,16) and where possible, effort needs to be made to capture their liking. Prior work by this team has identified that persons with dysphagia who have sufficiently adequate cognition can communicate their preferences with the modified Cued Facial Scale (16).…”
Section: Sensory Resultsmentioning
confidence: 99%
“…Prior work by this team has identified that persons with dysphagia who have sufficiently adequate cognition can communicate their preferences with the modified Cued Facial Scale (16).…”
Section: Sensory Resultsmentioning
confidence: 99%
“…Before the tasting sessions, these terms were explained for the participants. In addition, previous studies have shown that old adults are able to differentiate between flavor and texture (Kremer, Mojet, & Kroeze, 2005) and flavor and appearance (Ettinger, Keller, & Duizer, 2014;Okkels, Dybdal, et al, 2018). Another strength of the study was the transportation and reheating of the meals, which were comparable to the meals-on-wheels system, where subsequently the meals should be tested in a randomized intervention study (Okkels, Dybdal, et al, 2018;Okkels, Saxosen, et al, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…Vision and auditory perception are reported to be the dominant features in human perception of food (Gnaedinger et al , ). The appearance of a meal in terms of the colour, taste and smell, all perceived by the orbitofrontal cortex involved in processing pleasant stimuli, and how it is served is shown to play an important role in the evaluation of foods among the elderly and dysphagics (Ettinger et al , ). As such, oral sensation holds the potential for making sensory modified foods for dysphagia management.…”
Section: Tribological and Sensory Attributes Of Tmfs For Dysphagia Mamentioning
confidence: 99%